Comparative Study of the Structural Properties for Thin and Thick ZnO Films Deposited on PPC Plastic Substrates. Issue 1 (July 2021) - Jandow, N. N.; Abbas, A.A.; Mohammed, Kh. G.; Habubi, N. F.; Yam, F.K.
Abstract: ZnO films with various thicknesses (0.4, 0.6, 0.8, 1 and 1.3 μm) had been prepared on PPC plastic bases by using DC sputtering. XRD results showed that all the films displayed principally ZnO (002) peak at 2θ = 34.115°, 34.01, 34.16, 34.07 and 34.12° with FWHM of 0.41°, 0.34, 0.27, 0.21 and 0.368° respectively, which is coincide with wurtzite hexagonal phase, indicated that films were preferentially grown along c-axis. XRD results also showed that the lattice constant and the crystallite size for the deposited thin films became larger than those for the thick film 1.3 μm; while the stress and microstrain increased for the thick films.